PERKEMBANGAN ILMU HUKUM PIDANA KORPORASI DIHUBUNGKAN DENGAN PENDIDIKAN HUKUM BERKELANJUTAN BAGI ADVOKAT - sirait, timbo mangaranap (Veritas et Justitia, 2017)
The growing sociological development of corporations that engage in criminal acts has led to various jurisdictions of the State designing policies on how to prevent and repress crime and protect the public. The implication of corporation criminal law is growing. This research conducted with normative juridical method, and concluded that The Advocate profession organizations needs to conduct continuous legal education on (candidate) advocate in cooperation with faculty of law, so that advocate as profession “Officium Nobile” can always awake his dignity because it can play a high role in law enforcement and justice in the latest.